COMMON ERROR IN ENGLISH COMPOSITION MADE BY THE THIRD YEAR STUDENTS OF SMPN 35 JAKARTA IN ACADEMIC YEAR 2010/2011 - Tsalatsatun Andini (Wanastra: Jurnal Bahasa dan Sastra, 2014)
This study has shed light on the manner in which students within the rules of the target language, which is english. This study examines errors in a corpus of 38 essays written by 38 participants. The participants are the third year students of SMPN 35, East Jakarta. They were asked to write an english essays then 10 scripts of the essays were chosen randomly for analyzing. All of the errors inthe essays were identified and classified into various categorization. The purposes of this study is to find the the error that mostly commited by the students. Descriptive method is used for analyzing the data and library research method is used for collecting the data. The result of this study shows that four most common errors committed by the participants were error in singular/plural form, error in the use of article, error in the use of pronoun, and error in subject/verb agreement. These aspects of writing in english pose the most difficult problems to participants.